Classificazione, inquadramento diagnostico e trattamento della lesione di Monteggia in età pediatrica - Gallone, G.; Trisolino, G.; Di Gennaro, G.T.; Antonioli, D.; Stilli, S. (Lo Scalpello - Journal, 2018)
CLASSIFICATION, DIAGNOSIS AND TREATMENT OF MONTEGGIA LESIONS DURING CHILDHOODMonteggia fractures represent the association of a fracture of the proximal ulna and luxation of the radial head. Thistype of lesion is infrequent and may be misdiagnosed, particularly in paediatric patients. Classification of theseinjuries is based on the scheme proposed by Bado and later supplemented by other authors to better discriminatedoubts and to guide the treatment. The treatment of choice of acute Monteggia lesions in the paediatric age is in mostcases conservative, and it involves reduction and immobilisation in a cast. Surgery is mostly reserved for complex casesand for inveterate lesions that represent a high risk for chronic disorders and disabling sequelae; in these cases, thechoice of treatment remains controversial. The aim of this article is to describe the anatomical-pathologicalcharacteristics, the diagnostic criteria, and the principles of treatment of Monteggia lesions in the paediatric age.